RHYOLITE MAGMA DEGASSING: AN EXPERIMENTAL STUDY OF MELT VESICULATION - Bagdassarov N.S.; Dingwell D.B.; Wilding M.C. (My University, 1996)
The vesiculation of a peralkaline rhyolite melt (initially containing ~0.14 wt.% H2O) has been investigated at temperatures above the rheological glass transition (Tg≈530 °C) by (a) in situ optical observation of individual bubble growth or dissolution and (b) dilatometric measurements of the volume expansion due to vesiculation. The activation energy of the timescale for bubble growth equals the activation energy of viscous flow at relatively low temperatures (650-790 °C), but decreases and tends towards the value for water diffusion at high temperatures (790-925 °C). The time dependence of volume expansion follows the Avrami equation ΔV (t)~{1-exp [-(t/τav)n]} with the exponent n=2-2.5. The induction time of nucleation and the characteristic timescale (τav) in the Avrami equation have the same activation energy, again equal to the activation energy of viscous flow, which means that in viscous melts (Peclet number <1) the vesiculation (volume expansion), the bubble growth process, and, possibly, the nucleation of vesicles, are controlled by the relaxation of viscous stresses. One of the potential volcanological consequences of such behavior is the existence of a significant time lag between the attainment of a super-saturated state in volatile-bearing rhyolitic magmas and the onset of their expansion.
Keywords: RHYOLITE; VESICULATION; KINETIC; WATER; DIFFUSION; DEGASSING